Metaphors Arab Women Live By - El-Aswad, el-Sayed (Hawwa, 2014)
The scholarship of metaphor as an analytical concept in the study of Arab society, in general, and Arab women, in particular, is woefully scarce. Based on ethnographic research in Egypt and United Arab Emirates, this paper discusses how culturally shared metaphors used by Arab women in their everyday lives reveal important cosmological and social features. The study refutes the claim that women serve as metaphors for men, while men do not perform a similar service for women. The inquiry is not an attempt to provide a comprehensive anthropological analysis of Arab women’s metaphors; rather it identifies specific gender-related metaphors constructing a system of conceptual symbols through which Arab women’s everyday life attains meaning. The research focuses on particular domains including marriage, food & nourishment, rootedness & authenticity, covering & protection and patience. The study concludes that metaphors used by Arab women are interrelated and rich conveying not only practical and concrete messages, but also expressive images and evaluative statements.